Batch Chemical Process Integration Analysis, Synthesis and Optimization - Majozi, Thokozani; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
(3z(BBatch Chemical Process Integration: Analysis, Synthesis and Optimization(3y (Bis an excellent source of information on state-of-the-art mathematical and graphical techniques for analysis, synthesis and optimization of batch chemical plants. It covers recent techniques in batch process integration with a particular focus on the capabilities of the mathematical techniques. There is a section on graphical techniques as well as performance comparison between graphical and mathematical techniques. Prior to delving into the intricacies of wastewater minimisation and heat integration in batch processes, the book introduces the reader to the basics of scheduling which is aimed at capturing the essence of time. A chapter on the synthesis of batch plants to highlight the importance of time in design of batch plants is also presented through a real-life case study. The book is targeted at undergraduates and postgraduate students, researchers in batch process integration, practising engineers and technical managers.s
to Batch Chemical Processes -- Short-Term Scheduling -- Process Intermediate Storage Operational Philosophy: The New Operational Philosophy -- Wastewater Minimisation in Multiproduct Batch Plants: Single Contaminants -- Storage Design for Maximum Wastewater Reuse in Batch Plants -- Wastewater Minimisation in Multipurpose Batch Plants: Multiple Contaminants -- Wastewater Minimisation Using Multiple Storage Vessels -- Zero Effluent Methodologies -- Wastewater Minimisation Using Inherent Storage -- Heat Integration in Multipurpose Batch Plants: I. Direct Heat Integration -- Heat Integration in Multipurpose Batch Plants: II. Indirect Heat Integration -- A Graphical Technique for Wastewater Minimisation in Batch Processes.
Keywords: Chemistry; Chemical engineering; Environmental chemistry; Chemistry; Industrial Chemistry/Chemical Engineering; Environmental Chemistry